2017
DOI: 10.1021/acs.est.7b00458
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Ibuprofen by Phragmites australis: Uptake and Phytodegradation

Abstract: This study explores ibuprofen (IBP) uptake and transformation in the wetland plant species Phragmites australis and the underlying mechanisms. We grew P. australis in perlite under greenhouse conditions and treated plants with 60 μg/L of IBP. Roots and rhizomes (RR), stems and leaves (SL), and liquid samples were collected during 21 days of exposure. Results show that P. australis can take up, translocate, and degrade IBP. IBP was completely removed from the liquid medium after 21 days with a half-life of 2.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(66 citation statements)
references
References 49 publications
(98 reference statements)
2
50
2
3
Order By: Relevance
“…In addition, it may be postulated that rapid phase III metabolism may have limited the accumulation of such conjugates in the plant tissues, making the conjugates transient metabolites. In previous studies, glycosyltransferase was observed to catalyze the detoxification of ibuprofen in Phragmite australis during a 21 d exposure (He et al, 2017). Further, the formation of a glucose conjugate has been considered to be a major detoxification pathway for several environmental contaminants (e.g., Ando et al, 2015;Fu et al, 2017aFu et al, , 2017b.…”
Section: Diazepam-induced Changes To Glycosyltransferase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it may be postulated that rapid phase III metabolism may have limited the accumulation of such conjugates in the plant tissues, making the conjugates transient metabolites. In previous studies, glycosyltransferase was observed to catalyze the detoxification of ibuprofen in Phragmite australis during a 21 d exposure (He et al, 2017). Further, the formation of a glucose conjugate has been considered to be a major detoxification pathway for several environmental contaminants (e.g., Ando et al, 2015;Fu et al, 2017aFu et al, , 2017b.…”
Section: Diazepam-induced Changes To Glycosyltransferase Activitymentioning
confidence: 99%
“…Several studies have focused on the uptake and accumulation of pharmaceuticals in agricultural plants as a result of TWW irrigation (e.g., Wu et al, 2013Wu et al, , 2014Goldstein et al, 2014;Carter et al, 2014). These studies have demonstrated the capacity of higher plants to take up these compounds; however, until recently, relatively little consideration has been given to their metabolism in plants (Fu et al, 2017a(Fu et al, , 2017bHe et al, 2017;Huber et al, 2009Huber et al, , 2012Wu et al, 2015). Recent studies have shown that higher plants can metabolize xenobiotics similarly to humans with phase I modification reactions followed by phase II conjugation reactions using detoxification enzymes that function as a 'green liver' (Sandermann, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The plants in CWs fulfill various purposes. Plants can directly remove contaminants by actively taking them up in their biomass, accumulating them and enzymatically breaking them down (He et al, 2017;Hurtado et al, 2016;Malchi, Maor, Tadmor, Shenker, & Chefetz, 2014). Plants also indirectly influence the removal of components by excreting exudates, nutrients and oxygen for microorganisms in the rhizosphere, thus stimulating microbial degradation (Garcia et al, 2010;Zhai, Piwpuan, Arias, Headley, & Brix, 2013).…”
Section: Plant Uptakementioning
confidence: 99%
“…The exact removal mechanism for specific contaminants in CWs was not further elucidated. However, several groups recently have worked on identifying specific CW removal mechanisms for mixtures of different contaminants ( Avila, Reyes, Bayona, & Garc ıa, 2013;He, Sutton, Rijnaarts, & Langenhoff, 2018;He et al, 2017;Matamoros, Garc ıa, & Bayona, 2008;Petrie et al, 2018;Zhang, Gersberg, Ng, & Tan, 2014), which allows a better prediction of the fate of CC from CTBD in the CW. In addition to the removal mechanisms, important parameters that influence CW functioning will be discussed, and challenges for the implementation of CWs for the removal of CC from CTBD will be identified.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, reclaimed wastewater counts for 50% of the total irrigation water used in Israel and also within the European Union, countries like Spain or Italy use substantial amounts of reclaimed water . For this reason the uptake, translocation and metabolization of xenobiotics by plants is the topic of a series of research projects reflected in a number of corresponding publications .…”
Section: Introductionmentioning
confidence: 99%